Beyond Graphene Anode Materials for Emerging Metal Ion Batteries and Supercapacitors - Mukherjee, Santanu; Ren, Zhongkan; Singh, Gurpreet (Nano-Micro Letters, 2018)
Intensive research effort is currently focused on the development of efficient, reliable, and environmentally safe electrochemical energy storage systems due to the ever-increasing global energy storage demand. Li ion battery systems have been used as the primary energy storage device over the last three decades. However, low abundance and uneven distribution of lithium and cobalt in the earth crust and the associated cost of these materials, have resulted in a concerted effort to develop beyond lithium electrochemical storage systems. In the case of non-Li ion rechargeable systems, the development of electrode materials is a significant challenge, considering the larger ionic size of the metal-ions and slower kinetics. Two-dimensional (2D) materials, such as graphene, transition metal dichalcogenides, MXenes and phosphorene, have garnered significant attention recently due to their multi-faceted advantageous properties: large surface areas, high electrical and thermal conductivity, mechanical strength, etc. Consequently, the study of 2D materials as negative electrodes is of notable importance as emerging non-Li battery systems continue to generate increasing attention. Among these interesting materials, graphene has already been extensively studied and reviewed, hence this report focuses on 2D materials beyond graphene for emerging non-Li systems. We provide a comparative analysis of 2D material chemistry, structure, and performance parameters as anode materials in rechargeable batteries and supercapacitors. Highlights: 1 A comprehensive review of novel 2D materials, particularly MXene and phosphorene, for applications as electrodes in both batteries and supercapacitors. The performance of these materials, in addition to their fabrication techniques, structure, and electrochemistry, is highlighted. 2 Separate sections are dedicated to explaining the limitations of conventional anode materials and the role of 2D materials in addressing these deficiencies, in addition to the future path of development of this field of research.